Irradiation effect in WO3 thin films - Zayim, Esra Ozkan; Baydogan, Nilgün Dogan (Elsevier BV, 2006)
Abstract Tungsten oxide (WO 3 ) films were prepared on indium tin oxide coated glass substrates and Corning glass substrates by sol–gel deposition. The samples coated on the glass substrates have been irradiated to approximately 0.93–21.1 kGy dose using Co-60 gamma radioisotope. Co-60 radioisotope changed the color of the WO 3 films on samples after the irradiation. Their color turned to brownish color tones depending on the applied dose. Optical and structural properties of the samples are examined for both gamma irradiated and unirradiated coated samples. To compare the effect of the irradiation on the electrochromic properties, additional measurements were done with WO 3 coated on ITO substrates irradiated by gamma rays, separately. The coated films were characterized by atomic-force microscopy, NKD-analyzer and cyclic voltammograms. The influence of irradiation on the spectra of transmittance and on the surface structure has been investigated. These showed that the surface texture was changed dramatically by the irradiation. The electrochemical insertion and removal of lithium and proton ions was carried-out using 1  M LiClO 4 propylene carbonate (PC) electrolyte and 1  M KCl in aqueous solutions,respectively.